Exploring The Beliefs Of Academic Self-Efficacy Among Undergraduate Male Engineering Students - Touseef Fatima, Kiran Hashmi (Pakistan Journal of Educational Research, 2020)
Self-efficacy entails the belief of an individual in oneself for the accomplishment of a specific task. The study investigated sources as well as perceptions that promoted the development of academic self-efficacy of undergraduates. The phenomenological approach employed to analyze the perceptions of undergraduate male engineering students. As phenomenology found compatible with undergraduate students to explain their feelings, experiences, and thoughts about returning to obtain their engineering degree in university after being dropped out. Five participants from private Sindh chartered university responded through an adapted semi-structured interview that reflected their responses on the components of self-efficacy; (a) performance experience, (b) vicarious learning, (c) verbal persuasion, (d) affective states and physical sensation. The data was analyzed by thematization. The findings of the study suggested that components of self-efficacy were the strongest predictors for undergraduate male students who had been dropped out of university to eventually return to earn their engineering degree in university. Furthermore, the study also explored those perceptions about components of self-efficacy that provided a framework to learn those experiences that impact on the academic success of undergraduate male students who had dropped out of university to eventually return to earn their engineering degree in university.